Developing new predictors of Helicobacter pylori associated disease and its progression - White, Jonathan Richard (2017)
Since discovery H. pylori has been one of the most intensively researched bacteria. Although the majority of those infected remain asymptomatic it can lead to serious diseases which carry significant morbidity and mortality. The most serious complication of H. pylori infection is gastric cancer and one of the most effective ways to reduce the associated mortality is to detect pre-malignant disease, as this develops in a step wise manner.